The potency of bioactive constituents in Piper betle L. for Alzheimer Targeting on Caspase-3 - in silico studies - Putri, Anindya Calista Nabila; Ashriany, Raissa Rerey; Salsabila, Sitti Kesya; Rahmaharva, Naila Dwi; Muljono, Fajar Oktavian; Fardhan, Firghi Muhammad; Novitasari, Dhania (Journal of Pharmaceuticals and Natural Sciences, 2024)
Alzheimer’s disease (AD) is a neurodegenerative condition that can disrupt memory, cognition, and neurological functions, Recent studies highlight caspase-3 as a potential target, with several lines of evidence pointing to the enzyme's possible role in the onset of AD. Several findings revealed that betel leaf was also examined to treat AD by targeting acetylcholinesterase in vitro and in silico, yet no evaluation had not been done in caspase-3 activity. Using molecular docking, Lipinski's and PreADMET prediction, an in-silico analysis of compounds found in betel leaf (Piper betle L.) was conducted in order to determine whether these compounds could be applied as therapeutic candidates in the treatment of Alzheimer's. To ascertain the drug similarity and ADMET profile of the evaluated ligands, the Mcule and PreADMET sites were used in the studies, which were followed by the molecular docking simulation software AutoDock. The findings demonstrated that all the tested compounds passed the physicochemical features based on Lipinski rule. Further analysis then showed that arecoline bound to the critical amino acid that involved in caspase-3 inhibition. Further evaluation needs to be done to confirm the molecular mechanism of P. betle leaves to AD.